Perceptions of the Coach–Athlete Relationship Predict the Attainment of Mastery Achievement Goals Six Months Later: A Two-Wave Longitudinal Study among F. A. Premier League Academy Soccer Players - Nicholls, Adam R.; Earle, Keith; Earle, Fiona; Madigan, Daniel J. (Frontiers in Psychology, 2017)
All football teams that compete within the F. A. Premier League possess an academy, whose objective is to produce more and better home-grown players that are capable of playing professionally. These young players spend a large amount of time with their coach, but little is known about player’s perception of the coach–athlete relationship within F. A. Premier League Academies. The objectives of this study were to examine whether perceptions of the coach–athlete relationship changed over six months and if the coach–athlete relationship predicted self-reported goal achievement among F. A. Premier League academy players. This study included cross-sectional (n = 104) and longitudinal (n = 52) assessments, in which academy soccer players completed a measure of the coach–athlete relationship and goal achievement across either one or two time periods. The cross-sectional data were subjected to bivariate correlations, whereas the longitudinal data were analyzed using multiple regressions. Perceptions of the coach–athlete relationship remained stable over time. The coach–athlete relationship predicted the achievement of mastery goals six months later. Enhancing the quality of the coach–athlete relationship among elite adolescent athletes appears to be a suitable way of maximizing mastery achievement goals, particularly among developmental athletes who participate in team sports.